Faktor Penentu Loyalitas Pelanggan Gojek Di Kota Yogyakarta: Peran Citra Merek, Kualitas Pelayanan, Dan Kepercayaan Dengan Kepuasan Sebagai Mediator - Ningrum, Natalia Ratna; Yogik, Muhamad Azrul (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
The main objective of this study is to find out how customer happiness mediates the relationship between Gojek brand image, service quality, and customer trust. The location of this study is Yogyakarta. A total of one hundred people participated in this quantitative study, which used a random sampling technique. Questions were asked to collect information. We used PLS (Partial Least Squares) to view the data. Although customer satisfaction is positively influenced by brand image and service quality, none of these factors contribute to consumer loyalty, according to the study findings. Customer trust does not affect customer satisfaction or loyalty. Customer happiness has been shown to mediate the relationship between brand image and service quality on customer loyalty. Although data is limited, customer satisfaction appears to link customer trust and loyalty.